Exploiting λ‐Orthogonal Photoligation for Layered Surface Patterning. Issue 3 (20th December 2017) - Lederhose, Paul; Abt, Doris; Welle, Alexander; Müller, Rouven; Barner‐Kowollik, Christopher; Blinco, James P.
Abstract: We exploit λ‐orthogonal photoligation of nitrile imine‐mediated tetrazole‐ene cycloaddition (NITEC) chemistry to generate complex, interconnected surface modifications via a simple layered surface patterning approach. By judicious choice of activating chromophores, we introduce a one pot reaction where nitrile imine formation can be triggered independently of other tetrazoles present. When irradiated with visible light, a tetrazole bearing a pyrene chromophore undergoes quantitative elimination of nitrogen to release nitrile imine (which subsequently undergoes trapping with a dipolarophile in a 1, 3 dipolar cycloaddition) whereas a tetrazole bearing a phenyl moiety remains unreacted. Subsequent irradiation of the solution with UV light yields the N ‐phenyl containing nitrile imine quantitatively, while the pyrene pyrazoline adduct remains unchanged. This λ‐orthogonal photoligation was subsequently exploited for the generation of layered patterned surfaces. Specifically, the visible light active tetrazole was grafted to a silicon wafer and subsequently photolithographically patterned with a dipolarophile modified with a UV‐active tetrazole. Various electron deficient olefins were then patterned in a spatially resolved manner relying on different light activation. The desired functionality was successfully imaged on the silicon wafers using time‐of‐flight–secondary ion mass spectrometry (ToF‐SIMS), demonstrating that a powerful mask‐less lithographic platform technology has been established. Abstract : λ‐Orthogonal printing : We exploitλ ‐orthogonal photoligation to generate complex, interconnected patterns via a simple layered NITEC approach. By judicious choice of activating chromophores, we introduce a one pot reaction where nitrile imine formation can be triggered independently.